2005
DOI: 10.1021/ie050490+
|View full text |Cite
|
Sign up to set email alerts
|

CFD Modeling of the Hydrodynamics and Reaction Kinetics of FCC Fluidized-Bed Reactors

Abstract: The hydrodynamics and reaction kinetics of gas-solid fluidized beds containing fluid catalytic cracking (FCC) particles were simulated using computational fluid dynamics (CFD). Drag models of Gidaspow and Syamlal and O'Brien overestimated the drag force for the FCC particles and predicted a greater bed expansion in comparison to the experimental data. The modified Syamlal-O'Brien drag model based on the minimum fluidization conditions of the FCC particles predicted the expected bubbling fluidization behavior a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
110
2
3

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 172 publications
(127 citation statements)
references
References 23 publications
12
110
2
3
Order By: Relevance
“…There is no effect for different values of restitution coefficient (e), friction coefficient (μ f ) and Hamaker constant (A). From fig.1 (a), it can be seen that the normal particle-particle interaction does not affect the bubble characteristics, and even in case of e=1, bubbles can still be clearly detected, which is in agreement with previous simulation results for Geldart A particles using a two-fluid modeling (Wang et al, 2009a;Zimmermann and Taghipour, 2005), and is clearly different from the DPM results for coarse particles, where it was shown that particle collision properties have a profound effect on bed hydrodynamics, where in case of e=1, no two-phase structure emerges at all (Li and Kuipers, 2007). Figure.1 Snapshots of simulation results taken at a slit (the particles located at the dimensionless bed depth between 0.35 and 0.65 are shown).…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…There is no effect for different values of restitution coefficient (e), friction coefficient (μ f ) and Hamaker constant (A). From fig.1 (a), it can be seen that the normal particle-particle interaction does not affect the bubble characteristics, and even in case of e=1, bubbles can still be clearly detected, which is in agreement with previous simulation results for Geldart A particles using a two-fluid modeling (Wang et al, 2009a;Zimmermann and Taghipour, 2005), and is clearly different from the DPM results for coarse particles, where it was shown that particle collision properties have a profound effect on bed hydrodynamics, where in case of e=1, no two-phase structure emerges at all (Li and Kuipers, 2007). Figure.1 Snapshots of simulation results taken at a slit (the particles located at the dimensionless bed depth between 0.35 and 0.65 are shown).…”
Section: Resultssupporting
confidence: 90%
“…However, only few studies are devoted to the hydrodynamics of Geldart A particles in BFBs, where all of them are based on TFM simulations. From those studies, a completely different picture as compared to B-and D-type particles emerged, namely, the restitution coefficient has no effect on the bubbling characteristics (Zimmermann and Taghipour, 2005), bed expansion characteristics (Wang et al, 2009b), minimum bubbling velocity and axial solid volume fraction profiles (Wang et al, 2009a). In these studies, the KTGF was used to represent the particle-particle interaction, which does include the effect of dissipation in collisions, but not the effect of particle-particle friction and/or inter-particle cohesive forces.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, the results did not support the previously proposed criteria (i.e. adequacy of mesh size less than or equal to 10 times the particle diameter) in the literature, [8,11], for CFD simulation of fluidized beds. Table 1 compares the time required for 20 s of real-time simulation.…”
Section: Grid Size Sensitivity Analysiscontrasting
confidence: 95%
“…However, before studying the actual co-firing performance, the basic gas-solid hydrodynamics of coal and biomass mixture is required to be investigated thoroughly. Most of the hydrodynamic studied on fluidized bed system available in open literature deal with mono-dispersed particles (Witta et al 1998;Zimmermann et al 2005;Deen et al 2006;Yu et al 2007;Zhu et al 2008;Armstrong et al 2010;Wang et al 2010;Sau et al 2011;Loha et al 2012;Cloete et al 2013). There are very few studies available on the fluidized bed hydrodynamics of mixture of particles having different diameters and/or densities.…”
Section: Introductionmentioning
confidence: 99%